A Comparative Study of the Effects of Valproate and Oxcarbazepine on Sexual Function, Sperm Quality, and Sex Hormones in Males with Epilepsy. (5th July 2021) - Guo, Yi; Chen, Lang; Wu, Dongmei; Yu, Liang; Sun, Hongbin; Zhu, Qiong
Abstract : Aims . Although several studies have indicated that valproate (VPA) and oxcarbazepine (OXC) cause reproductive endocrine disorders and sexual dysfunction, there remains some controversy regarding these issues in males with epilepsy. This study is aimed at evaluating the effects of VPA and OXC on sexual function, sperm quality, and sex hormones in young males with epilepsy. Methods . Males with newly diagnosed epilepsy treated with VPA and OXC were recruited, and sexual function questionnaires (International Index of Erectile Function-5 (IIEF-5)), sperm quality, and sex hormone levels were assessed before treatment and at 6 months after treatment with VPA or OXC monotherapy. Results . Forty-four young males with epilepsy (23 treated with VPA, 21 treated with OXC) and 30 age-matched healthy individuals were recruited for our study. The sexual function, sperm quality, marriage rate, and fertility rate of these young males with epilepsy were lower than those of healthy controls. Sperm quality were significantly reduced in young male patients after 6 months of VPA administration. The level of follicle stimulating hormone (FSH) was increased in patients after OXC treatment. Meanwhile, sexual function and sperm quality were not affected. Conclusion . Sexual function and sperm quality were reduced in young males with epilepsy. VPA may exert a negative effect on sperm quality, whereas OXC has no harmful effect on sexual function and sperm quality in young males with epilepsy.